Collaboration and Managing Risks within the Extended Supply Chain - Abu Al-Neel, Basil (2009)
As global markets continue to grow efficiently, ‘the rules of the game’ are constantly changing. New business trends, specifically within the supply chain area are being introduced over short periods of time, and the business environment is becoming increasingly competitive in a way that competition is no longer taking place among individual businesses, but among entire supply chains. As a result, Organisations need to improve their level of understanding with respect to what they are likely to face in the near future in terms of risks and challenges, how can knowledge be managed and acquired from internal and external sources to increase an organisation’s capabilities in handling risks and gaining competitive advantage in the market, in addition firms should understand the urging need of creating a collaborative relationship with their partners aimed at synchronising their efforts towards achieving mutual long-term goals and competing threats as a single unit.